2022
DOI: 10.14701/ahbps.22-044
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, mortality, and survival of liver cancer using Korea central cancer registry database: 1999-2019

Abstract: Invited ArticleBackgrounds/Aims: Historically, incidence and survival analysis and annual traits for primary liver cancer (LC) has not been investigated in a population-based study in Korea. The purpose of the current study is to determine incidence, survival rate of patients with primary LC in Korea. Methods: We conducted a retrospective cohort study using Korea Central Cancer Registry based on the Korea National Cancer Incidence Database. Statistical analysis including crude rate and age-standadized rate (AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…According to recent studies examining the trends in liver cancer in Korea over the past 20 years, it is evident that increased early detection of hepatocellular carcinoma has led to an improvement in the 5-year survival rate among patients undergoing surgical treatment [9][10][11]. Surgeons utilize numerous techniques to reduce blood loss during partial liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies examining the trends in liver cancer in Korea over the past 20 years, it is evident that increased early detection of hepatocellular carcinoma has led to an improvement in the 5-year survival rate among patients undergoing surgical treatment [9][10][11]. Surgeons utilize numerous techniques to reduce blood loss during partial liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…Initial treatment within 4 months of diagnosis was categorized as surgical (surgery alone, surgery with chemotherapy, surgery with radiotherapy, or surgery with chemotherapy and radiotherapy), non‐surgical (chemotherapy alone, radiotherapy alone, or chemotherapy and radiotherapy), and no active treatment information. Transcatheter arterial chemoembolization was included into the non‐surgical group 40,41 …”
Section: Methodsmentioning
confidence: 99%
“…Transcatheter arterial chemoembolization was included into the nonsurgical group. 40,41 Furthermore, given prior research that reported the predictive utility of the FIB-4 score for non-HCC cancers, [42][43][44] we also conducted further investigations to assess the ability of the FIB-4 in predicting breast cancer and colorectal cancer.…”
Section: Identification Of Hcc and Non-hcc Cancer Casesmentioning
confidence: 99%
“…The overall survival (OS) of patients with primary liver cancer is gradually improving [ 5 ]. However, the incidence of liver cancer is steadily increasing [ 6 , 7 ]. More centers are accepting LLR for primary liver cancer, following the first consensus meeting, which suggested that only tumors located in the anterolateral segments can be safely resected [ 8 ].…”
Section: Introductionmentioning
confidence: 99%